2017
DOI: 10.1021/acs.chemmater.7b03911
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Metal Oxide Aerogels

Abstract: In this study we report on mechanical properties of molded, single component Al 2 O 3 , Ga 2 O 3 , Fe 2 O 3 , and ZrO 2 as well as mixed aerogels, made from yttrium stabilized zirconia, yttrium aluminum garnet, and zinc aluminum spinel. Initially all aerogels were produced equally in molded bodies by a facile epoxy method and were annealed afterward at 300 °C. Then we performed uniaxial pressure tests on cylindrical aerogel monoliths to gain Young's modulus which depends on composition, density, and posttreatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 50 publications
1
40
0
Order By: Relevance
“…In fact the studies of mechanical properties have been reported only for organic aerogels, 44,45 carbon aerogels 46,47 or silica aerogels 48,49 and recently for other metal-oxide aerogels. 50 In this work a compression test was employed to evaluate the mechanical stability of silica shell modified and unmodified NANONETSs. As the dimensions of the NANONETS are small, and as the forces the samples are subjected to are also very small, it is not possible to actually measure the Young's modulus (which is usually done in the area of elastic deformation at low strain levels).…”
Section: Resultsmentioning
confidence: 99%
“…In fact the studies of mechanical properties have been reported only for organic aerogels, 44,45 carbon aerogels 46,47 or silica aerogels 48,49 and recently for other metal-oxide aerogels. 50 In this work a compression test was employed to evaluate the mechanical stability of silica shell modified and unmodified NANONETSs. As the dimensions of the NANONETS are small, and as the forces the samples are subjected to are also very small, it is not possible to actually measure the Young's modulus (which is usually done in the area of elastic deformation at low strain levels).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the main‐group metal oxide aerogels (i.e., SiO 2 , ZrO 2 , A1 2 O 3 , Ga 2 O 3 ), are typically prepared through the sol–gel transition from metal alkoxides precursors and subsequent supercritical drying. [ 30–33 ] However, the metal alkoxides are usually toxic and expensive, and the overall fabrication process is high energy‐consuming. [ 34 ] More importantly, low‐valence state transition‐metal alkoxides (e.g., Co, Ni, Mn) have poor stability and fast hydrolysis rate, inevitably resulting in the collapse of the pore structure and uncontrollable particle size of as‐prepared TMO aerogels.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of inorganic coatings can be created depending on the precursors used. For example, the hydrolysis of titanium isopropoxide resulted in a titanium dioxide matrix (Kim et al, 2011 ; Li et al, 2011 ; Hamid et al, 2014 ; Ge et al, 2015 ); iron (III) nitrate–iron (III) oxide matrix (Sun et al, 2005 , 2018 ; Hassan et al, 2013 ; Wan et al, 2015 ); and also probably the creation of ZrO 2 , HfO 2 , and Ta 2 O 5 oxide gels (Miller and Ko, 1996 ; Benad et al, 2018 ; Kiselev et al, 2019 ). Fixing elemental oxide on CNTs or CNFs surfaces changes hybrid materials characteristics.…”
Section: Synthesis Of Hybrid Materialsmentioning
confidence: 99%